Ent Examination and Cerumen Removal in Letjen Jamin Ginting Junior High School, Berastagi - Farhat, Farhat; Daulay, Elvita Rahmi; Darlan, Dewi Masyithah (Talenta Publisher, 2019)
Diseases of ear, nose, and throat (ENT) are common diseases in the world. The diseases are essential due to morbidities, which affect the physiological functions in the head and neck region. Cerumen impaction is the most common finding disease of ENT in children. The community service was done to find the distribution of ear, nose, and throat examination results of students in Letjen Jamin Ginting Junior High School, Berastagi, especially cerumen impaction which then were treated with cerumen removal. The community service also aimed to increase student's knowledge about ENT disease. The ENT examination was done to 188 students. The students with cerumen impaction were treated with cerumen removal. The students also educated about ENT disease to improve knowledge about ENT disease. Among 188 students, the number of male students was more than female with 98 students (52.1%), where 76 students (40.4%) were 14 years old. 150 students (79.8%) did not have any complaint about their ear, nose, and throat. Ear fullness was a common chief complaint from the students with 15 students (8.0%). Ear disease was a frequent disease with 44 students (47.3%) and cerumen impaction as the most common findings with 43 students (22.9%). In ENT disease education, the evaluation was done with the highest result was get by 8 students with 80% corrected answers. Ear disease had high prevalence with cerumen impaction as the most common findings of ENT examination.